76.4k views
0 votes
When -2 is substituted for x, in the equation y=x2+1 what is y.

User Prikha
by
5.5k points

2 Answers

3 votes

Answer:

y = -3

Explanation:

plug in the x value, y = -2(2) + 1

simplify, y = -4 + 1

simply again, y = -3

we can plug the y and x in to make sure it is equal

-3 = -2(2) + 1

simplify, -3 = -4 + 1

simplify again, -3 = -3

add 3 to both sides, 0 = 0

one possible answer is -3 for y, and -2 for x

User PriestVallon
by
4.9k points
4 votes

Answer:

5

Explanation:

1) so lets substitute -2 as x:

y=(-2)^2+1

(-2)^2=-2*-2=4

hence

y=4+1

y=5

Hope this helps

User Robert Brooker
by
5.1k points